Case Report: Rechallenge With BRAF and MEK Inhibitors in Metastatic Melanoma: A Further Therapeutic Option in Salvage Setting? - Stagno, Anna; Vari, Sabrina; Annovazzi, Alessio; Anelli, Vincenzo; Russillo, Michelangelo; Cognetti, Francesco; Ferraresi, Virginia (Frontiers in Oncology, 2021)
Background: The combination of BRAF and MEK inhibitors represents the standard of care treatment for patients with metastatic BRAF-mutated melanoma, notwithstanding the high frequency of emergent resistance. Moreover, therapeutic options outside clinical trials are scarce when patients have progressed after both targeted therapy and therapy with immune checkpoint inhibitors. In this article, we report our experience with targeted therapy rechallenging with BRAF and MEK inhibitors in patients with metastatic BRAF-mutated melanoma after progression with kinase inhibitors and immunotherapy. Methods: Four patients with metastatic BRAF-mutated melanoma were rechallenged with BRAF and MEK inhibitors after progression with targeted therapy and subsequent immunotherapy (checkpoint inhibitors). Results: Two patients (one of them was heavily pretreated) had partial response over 36 months (with local treatment on oligoprogression disease) and 10 months, respectively. A third patient with multisite visceral disease and high serum levels of lactate dehydrogenase had a short-lived clinical benefit rapidly followed by massive progression of disease (early progressor). The fourth patient, currently on treatment with BRAF/MEK inhibitors, is showing a clinical benefit and radiological stable disease over 3 months of therapy. Adverse events were manageable, similar to those reported during the first targeted therapy; the treatment was better tolerated at rechallenge compared with the first treatment by two out of four patients.